Analisis Rugi-Rugi Panas pada Tangki Penyimpan Panas dalam Sistem Pembangkit Listrik Tenaga Matahari - Pikra, Ghalya; Salim, Agus; Admono, Tri; Devi, Merry Indahsari (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2010)
Analysis of heat loss on heat storage tank in solar power generation system is intended to determine the heat loss value during storage. Selection of insulation material, insulation thickness, time of storage and heat storage fluid affects the heat losses. The research was initiated by determining the dimension of the tank and its insulation material, and determining the heat storage time in the tank. Fluid and operating temperature is determined to get the fluid specification to be used as data analysis. The analysis begins with the calculation of storage capacities, followed by making of thermal nets to get the thermal resistance equation which is then used to calculate the heat loss in the tank. The result shows that the heat storage tank with 0.4 m diameter and 0.45 m height and uses ceramic fiber wool insulation with 0.1m thickness gives the value of heat loss of 63.43 W.Â